2017
DOI: 10.1111/dgd.12362
|View full text |Cite
|
Sign up to set email alerts
|

Avian brains: Insights from development, behaviors and evolution

Abstract: Birds are an extensively specialized animal group with unique anatomical, physiological and ecological characteristics. Sophisticated social behaviors and remarkable cognitive abilities are present in several avian lineages, driven by their enlarged brains and intricate neural networks. These unique traits could be a result of adaptive evolution under the wide range of environmental constraints; however, the intrinsic mechanisms of avian brain development and evolution remain unclear. Here, we introduce recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 131 publications
0
23
1
Order By: Relevance
“…The recent studies on the oriental tit's responses to snakes (Ha et al, ; Suzuki, , , , ; current study) suggest a new avenue of research on birds. Considering recent advances in avian phylogenetics (Prum et al, ) and cognition (Nomura & Izawa, ; Ten Cate et al, ), we propose that the ideas suggested by Isbell (Isbell, , ) and other hypotheses about the special role of snake predation in the evolution of prey can be explored and tested in studies on birds through species‐level comparisons in those avian families that include species living in regions of high snake predation or low snake predation, as well as through family‐level comparisons between families that evolutionarily originated in snake‐rich or snake‐poor regions.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies on the oriental tit's responses to snakes (Ha et al, ; Suzuki, , , , ; current study) suggest a new avenue of research on birds. Considering recent advances in avian phylogenetics (Prum et al, ) and cognition (Nomura & Izawa, ; Ten Cate et al, ), we propose that the ideas suggested by Isbell (Isbell, , ) and other hypotheses about the special role of snake predation in the evolution of prey can be explored and tested in studies on birds through species‐level comparisons in those avian families that include species living in regions of high snake predation or low snake predation, as well as through family‐level comparisons between families that evolutionarily originated in snake‐rich or snake‐poor regions.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ramphastidae specimens have two conspicuous lumps ventrocaudally to the bulbus olfactorius (Figures 5d, 7d). Due to the position, these might belong to the mesopallium or the nidopallium, both regions involved in learning and memory process (Nomura & Izawa, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The design of the proposed artificial intelligence paradigm is motivated by the intelligent pattern in which birds are observed to utilize the airspace. Birds demonstrate a high level of intelligence leading to the study of cognitive ornithology and avian intelligence [33][34][35]. Fox in [36] recognize that avian intelligence play an important role in the design of future multiintelligence systems.…”
Section: Proposed Solution -Artificial Intelligencementioning
confidence: 99%